Solubility and solubilization in aqueous media - Yalkowsky, Samuel H. (Samuel Hyman), 1942- (American Chemical Society ; Oxford University Press, 1999)
"Written for both new and experienced researchers in pharmaceuticals, this book gives the reader a working knowledge of the various means of controlling the solubility and dissolution rates of drugs and other biologically active compounds."--BOOK JACKET. "The clarity of the presentation and the numerous examples make Solubility and Solubilization in Aqueous Media an invaluable guide for the working scientist."--BOOK JACKET.